An Analysis of Presupposition Triggers in â€œTurning Redâ€ - Dian Fitriani; Mhd. Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research analyzes the triggers of the presupposition that can be discovered in the movie "Turning Red." The purpose of this study is to identify the use of triggers of the presupposition that are employed in the movie "Turning Red." In the movie "Turning Red," there are several triggers of presupposition can be found. For this study, the researcher adopted Levinson's theory about the triggers of presupposition. A qualitative descriptive approach was adopted in this study. The data was gathered primarily through direct observation. Data were collected using a non-participatory approach, which meant the researcher was not present during data analysis. After doing the investigation, the researchers identified twenty items that function as the triggers of presupposition in the film Turning Red. The most prevalent triggers of presupposition in the film "Turning Red" are change-of-state verbs, iterative, and counterfactual conditionals. Each of them has three utterances. The second most common triggers of presupposition are implicative verbs, temporal clause, and cleft. Each of them has two utterances. There was only one utterance each sentence for definite description, factual verbs, comparisons and contrasts, nonrestrictive clauses, and wh-questions. There have been no discoveries about of judging verbs and implicit clefts with stressed constituents.